SIGNALING ACTIVATED BY THE DEATH RECEPTORS OF THE TNFR FAMILY - Andera, Ladislav (Biomedical papers, 2009)
Background: The fine balance in cellular life and death is affected by a number of tightly regulated, direct signals that can help to turn the balance either in favor of or against the ultimate fate. Among the most prominent players in the field of the extracellular signals leading to cell death, preferentially through induction of apoptosis belong several receptors from so-called Death Receptors group of the Tumour Necrosis Factors Receptors (TNFR) family.Methods and results: Over 15 years of the research on activation and regulation of the most prominent member of this group - receptors for the ligands TRAIL, FasL and TNFα brought not only a detail (and still refining) mechanism of these receptors activation and downstream signaling, but also connected them with the ultimate apoptotic gatekeeper - mitochondria. Mitochondria are, in addition to their essential role as the energy factories also repositories of a cavalry of apoptosis-inducing as well as regulatory proteins. However, in addition to the pro-death signaling, these receptors were also shown under certain circumstances to activate an opposite, pro-proliferative signaling as well as to participate in pro-inflammatory responses.Conclusions: Thus despite the concerned effort of a number of groups and thousands of published papers, novel roles for the intriguing group of these receptors and their ligands and fine tuning of their signaling still await to be uncovered. This cut-through review will be mainly focused on the prominent death-inducing members of this group - TNFR1, Fas/CD95 and TRAIL receptors.
Keywords: Keywords: Caspases/Necroptosis/Apoptosis/DISC/Death domain